Des élevages sous les fumées des industries du Creusot. La justice environnementale à rebours - Sandrine Petit (VertigO, 2019)
In the 1970s, smokes of the factories of Creusot-Loire, specialized in the manufacturing of steels, make sick the cattle which graze in surrounding pastures. The problem hits the headlines of the press in 1974. An experts’ committee is established. These experts agree on an excessive concentration of molybdenum in plants and soil, which, associated with a copper deficit, alters cattle health. The industrialists react by changing additives in the manufacturing process of steels and by putting in filters. If the term of justice is not used, the damage and harm are rehabilitated. The breeders finally got compensations, even if the expertise escapes them. Everything converges to say that justice was obtained, under the pressure of the farmers’ union and in a context where the environment is for its beginnings in politics. Nevertheless, nothing is said on the health of local residents, workers and farmers. This case comes to contribute to the works on the environmental justice well developed in the United States, more on urban areas. It illustrates a situation rarely considered of the relations between agriculture and industrial pollution in rural areas.